The Influence of Education Level, Work Motivation, and Work Experience on Employee Performance at CV Bina Duta Permata Bojonegoro - Shinta Mahmudah; R Yuniardi Rusdianto (Publik : (Jurnal Ilmu Administrasi), 2025)
This study aims to analyze and determine the effect of education level, work motivation, and work experience on employee performance at CV Bina Duta Permata Bojonegoro. Employee performance is an important factor in supporting organizational success and is strongly influenced by the quality of human resources. This research employs a quantitative approach using a survey method. Data were collected through questionnaires distributed to all employees of CV Bina Duta Permata Bojonegoro, totaling 30 respondents. The data analysis techniques used in this study include validity testing and reliability testing to ensure the quality of the research instruments, as well as classical assumption tests consisting of normality, multicollinearity, and heteroscedasticity tests. Furthermore, the data were analyzed using multiple linear regression analysis, coefficient of determination, F-test, and t-test. The results of the study indicate that education level, work motivation, and work experience simultaneously have a positive and significant effect on employee performance. Partially, education level has a positive and significant effect on employee performance. Likewise, work motivation and work experience each have a positive and significant effect on employee performance. Therefore, it can be concluded that improving employees’ education level, work motivation, and work experience can enhance employee performance at CV Bina Duta Permata Bojonegoro.